Antioxidant, Anti-Inflammatory, and Antibacterial Activities and Phytochemical Content of White Champaca (Michelia alba) Flower Extract - I Nyoman Jirna; I Nyoman Gede Suyasa; Cok Dewi Widya Hana Sundari; Nyoman Mastra; I Nyoman Purna Purna; Aprilia Rakhmawati (Medical Laboratory Technology Journal, 2026)
Michelia alba is a member of the Magnoliaceae family known to be rich in secondary metabolites with various biological activities. Multiple studies on related plants have shown that the flowers contain flavonoids, terpenoids, and phenolics that have potential as anti-inflammatory and antibacterial agents. The objectives of this study were to evaluate the phytochemical content of Michelia alba flower extracts and to determine their anti-inflammatory and antibacterial activities through an in vitro approach. Extraction was performed using the ethanol maceration method, followed by qualitative and quantitative phytochemical tests; quantitative phytochemical testing was performed using a UV-Vis spectrophotometer. Anti-inflammatory activity was tested using a UV-Vis spectrophotometer at a wavelength of 560 nm based on the membrane stabilization method, while antibacterial activity against Staphylococcus aureus was assessed using the disk diffusion method. The results showed that the extract contained flavonoids, phenolics, tannins, and saponins qualitatively, with a total phenolic content of 80.53 mg GAE/g , total tannin content of 122.32 mg TAE/g, and a total flavonoid content of 84.14 mg QE/g. Antioxidant test showed a content of 54.64 ppm (strong), anti-inflammatory test showed a potential with an average  98.90% (very strong), and antimicrobial potential in vitro with an inhibitory power of <15 mm with a variation of 5 mm - 10.25 mm. There was no difference in various concentrations (55%, 70%, 85%, and 100%) of white Michelia alba flower extract in inhibiting the growth of S. aureus, with a sig value = 0.095. The complex metabolite profile allows for synergistic effects between compounds, so that even though the inhibition zones are moderate, the biological activity remains pharmacologically relevant. Overall, this study shows that Michelia alba flower extract has significant potential as a candidate natural anti-inflammatory and antibacterial ingredient for the development of phytochemical-based products.